Exploration of the Antibacterial and Enzymatic Potential of Fungal Associated with Giant Clams (Hippopus hippopus Linnaeus, 1978) in Ambon Waters: - Eka Wulidanisa; Delianis Pringgenies; Wilis Ari Setyati (Jurnal Moluska Indonesia, 2026)
Marine fungi associated with giant clams (Hippopus hippopus) are a source of secondary metabolites with great potential in the development of antibacterial agents and enzyme producers. Exploration of fungi from marine organisms is important considering the increasing need for new bioactive compounds. This study aims to: (1) determine the potential antibacterial activity against test bacteria, (2) determine the potential proteolytic, amylolytic, and lipolytic enzyme activities. The research methods include isolation of fungi from clam tissue, antibacterial tests using the agar plug method against test bacteria Staphylococcus aureus, Escherichia coli, Staphylococcus epidermidis, Pseudomonas aeruginosa, and Cutibacterium acnes and enzymatic activity tests.Three isolates of giant clam-associated fungi (Hippopus hippopus) were isolated, namely SK1 10.4, SK1 10.6, and SK1 10.6.2. Antibacterial tests of the three isolates showed inhibitory activity against the growth of test bacteria. Isolate SK1 10.6 was the best candidate because it had stable antibacterial activity and a large inhibition zone. In addition, this isolate also showed protease enzymatic activity. Key word : Antibacterial; Enzymatic; Hippopus hippopus; Fungi; Molecular Jamur laut yang berasosiasi dengan kima (Hippopus hippopus) merupakan salah satu sumber metabolit sekunder yang berpotensi besar dalam pengembangan agen antibakteri dan penghasil enzim. Eksplorasi jamur dari organisme laut menjadi penting mengingat meningkatnya kebutuhan terhadap senyawa bioaktif baru. Penelitian ini bertujuan untuk: (1) mengetahui potensi aktivitas antibakteri terhadap bakteri uji, (2) mengetahui potensi aktivitas enzim proteolitk, amilolitik, dan lipolitik. Metode penelitian meliputi isolasi jamur dari jaringan kima, uji antibakteri menggunakan metode agar plug terhadap bakteri uji Staphylococcus aureus, Escherichia coli, Staphylococcus epidermidis, Pseudomonas aeruginosa, dan Cutibacterium acnes, serta uji aktivitas enzimatik. Jamur asosiasi kima (Hippopus hippopus) yang diisolasi sebanyak 3 isolat, yaitu SK1 10.4, SK1 10.6, dan SK1 10.6.2. Uji antibakteri ketiga isolat tersebut menunjukkan adanya aktivitas penghambatan terhadap pertumbuhan bakteri uji. Isolat SK1 10.6 sebagai kandidat terbaik karena memiliki aktivitas antibakteri yang stabil dan zona hambat yang besar. Selain itu, isolat ini juga menunjukkan aktivitas enzimatik protease. Kata kunci : Antibakteri; Enzimatis; Hippopus hippopus; Jamur; Molekuler